Evaluating the effect of emergent and competitive strategies on the relationship between market uncertainty and firm performance: The case of selected SME entrepreneurs associated with PDRF - Ang, Kathleen Mae Sim (Animo Repository, 2022)
The research paper aims to investigate whether emergent and competitive strategy has a mediating effect of on the relationship between market uncertainty and firm performance as perceived by selected SME Entrepreneurs associated with PDRF. It aims to answer the main question “What are the mediating effects of Strategies (emergent and competitive) on the Relationship of Market Uncertainty and Firm Performance as perceived by selected SME Entrepreneurs associated with PDRF?” and find out the relationships and effects of the different variables involved. For the methodology, the study followed a qualitative, descriptive, exploratory research design using an analytical method, specifically content analysis. In terms of data gathering, semi-structured interviews were conducted online through the video communication application Zoom, where the meeting links were sent through the informants’ emails. The interview was solely conducted for selected SME entrepreneurs that are associated with PDRF and industry experts in the field of strategic marketing and strategic management. The results show that there is a mediating effect of both emergent and competitive strategies towards the relationship between market uncertainty and firm performance. The results also showed that the variables all relate and affect one another. The researchers recommend SMEs associated with PDRF to always be prepared for uncertain occurrences and to be quick in creating effective emergent strategies. In addition, they should maintain their distinctive features through competitive strategies. With both strategies, firms should always monitor their finances and make sure that it is well-managed. Furthermore, firms should ensure that their market is satisfied in order to create a loyal customer base. Being open to changes and mistakes can help them choose the right course of action when facing challenges and uncertainties. For PDRF, the study can help them understand the insights and experiences of SMEs associated with their organization. It can also help them with the way they create and execute plans relating to training programs and other future activities that aims to help entrepreneurs and businesses grow. This research paper was able to give more insights and depth of how SMEs would create emergent and competitive strategies and see how it affects the relationship between market uncertainty and firm performance. However, the researchers would suggest having more interviewees to bring more insight and perspectives on the mediating effect emergent and competitive strategy would have on market uncertainty and firm performance since this study is limited to the selected SMEs who are associated with PDRF. Furthermore, future research could also focus on a more specific industry of location for the research locale as the researchers believe that there may be a different outcome.